Abundance and breeding distribution of seabirds in the northern part of the Danco Coast, Antarctic Peninsula - Gonzalez Zevallos, Diego Ricardo; Santos, Maria Mercedes; Rombola, Emilce Florencia; Juares, Mariana Alejandra; Coria, Néstor R. (Polar Research)
Seabird abundances and breeding distribution have the potential to serve as ecological indicators. The western Antarctic Peninsula is one of the three sites in the world with the greatest increases in local temperature during the last 50 years. The aim of this study was to monitor the distribution and abundance of breeding populations of seabirds in the northern sector of the Danco Coast, north-west of the Antarctic Peninsula, during the breeding season 2010/11. The birds were the Wilson?s storm petrel (Oceanites oceanicus), South Polar skua (Stercorarius maccormicki), kelp gull (Larus dominicanus), Antarctic tern (Sterna vittata), snowy sheathbill (Chionis alba), chinstrap penguin (Pygoscelis antarctica), southern giant petrel (Macronectes giganteus), gentoo penguin (Pygoscelis papua), Cape petrel (Daption capense) and Antarctic shag (Phalacrocorax bransfieldensis). Annual breeding population growth increased in pygoscelids,southern giant petrel and sheathbill, and for the remaining species, breeding population trends were stable. Given that seabird populations can provide valuable information on the conditions of their feeding and nesting environments, this study highlights the need to maintain basics monitoring studies. Fil: Gonzalez Zevallos, Diego Ricardo. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Nacional Patagónico; Argentina Fil: Santos, Maria Mercedes. Ministerio de Relaciones Exteriores, Comercio Interno y Culto. Dirección Nacional del Antártico. Instituto Antártico Argentino; Argentina Fil: Rombola, Emilce Florencia. Ministerio de Relaciones Exteriores, Comercio Interno y Culto. Dirección Nacional del Antártico. Instituto Antártico Argentino; Argentina Fil: Juares, Mariana Alejandra. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Ministerio de Relaciones Exteriores, Comercio Interno y Culto. Dirección Nacional del Antártico. Instituto Antártico Argentino; Argentina Fil: Coria, Néstor R. Ministerio de Relaciones Exteriores, Comercio Interno y ...